Effects of Feeding Dried Cashew Apple Pulp on Zootechnical and Economic Performances of Local Pigs on Station in The South of Senegal - Ayssiwede, Simplice Bosco; Atchiwassa, Sodjinin; Ossebi, Walter; Michihoun, Gael Sabin; Assani, Bilkiss V. M.; Missohou, Ayao (Indian Journal of Animal Nutrition, 2024)
This work carried out in Casamance region aims to evaluate the zootechnical and economic performances of diets containing dried cashew apple pulp (CAP) for local pigs. Conducted from December 2022 to April 2023, the trial involved 84 local piglets (including 39 castrated males) aged 3 to 5 months and weighing 11 kg average live weight (ALW). These piglets were randomly divided into 4 batches of 21 subjects each, subdivided into 3 replicates of 7 subjects, corresponding respectively to four (4) iso-nutritional dietary treatments, CAP0 (control), CAP10, CAP15 and CAP20 containing respectively 10, 15 and 20% of CAP, for fattening pigs. Raised in permanent confinement at 1.4 m2/pig, the piglets were identified, dewormed and fed ad libitum with these diets, all presented in meal form, and watered with tap drinking water. ALW, average daily gain (ADG), feed intake (FI), feed conversion ratio (FCR), carcass weights and dressings (CW and DC), and profit margins obtained per dietary treatment were processed and subjected to a one-factor ANOVA, completed by Duncan's posthoc test at 5% threshold. The results revealed no significant difference (p˃0.05) between the ALW, ADG and CW of pigs from different dietary treatments. The DFI of subjects in CAP0 and CAP15 were similar, but significantly (p